How special are they? Targeting systemic risk by regulating shadow banking - Tobias H. Tröger (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2014)
This essay argues that at least some of the financial stability concerns associated with shadow banking can be addressed by an approach to financial regulation that imports its functional foundations more vigorously into the interpretation and implementation of existing rules. It shows that the general policy goals of prudential banking regulation remain constant over time despite dramatic transformations in the financial and technological landscape. Moreover, these overarching policy goals also legitimize intervention in the shadow banking sector. On these grounds, this essay encourages a more normative construction of available rules that potentially limits both the scope for regulatory arbitrage and the need for ever more rapid updates and a constant increase in the complexity of the regulatory framework. By tying the regulatory treatment of financial innovation closely to existing prudential rules and their underlying policy rationales, the proposed approach potentially ends the socially wasteful race between hare and tortoise that signifies the relation between regulators and a highly dynamic industry. In doing so it does not generally hamper market participants' efficient discoveries where disintermediation proves socially beneficial. Instead, it only weeds-out rent-seeking circumventions of existing rules and standards.
urn:nbn:de:hebis:30:3-350018
Keywords: G21; G28; H77; K22; K23; L22; 330; shadow banking; regulatory arbitrage; prudential supervision